Frequency of Ventricular Tachycardia in First 48 Hours of ST-Elevation Myocardial Infarction: Ventricular Tachycardia in Myocardial Infarction - Ahmad Khan, Zahoor; Ali Khan, Kashif; Asghar Khan, Muhammad; Aslam Awan, Zahid (Pakistan Journal of Health Sciences, 2023)
ST-elevation myocardial infarction (STEMI) has a poor long-term prognosis associated with early ventricular tachycardia (VT). Objective: To find out the frequency of ventricular tachycardia in the first 48 hours of ST-elevation myocardial infarction. Methods: After approval from the Hospital ethical committee, the study was conducted in the department of cardiology Hayatabad medical complex Peshawar from 1st October 2020 to 31st March 2021. All the patients having new onset ST-elevation Myocardial infarction as per Operational definition, both genders, aged between 40 and 75 years and who have given consent were included in the study. Non-probability consecutive sampling technique is being used for the sampling. Results: Standard deviation was ±1.357 years, while the average age was 51.56. Gender-wise distribution among patients male was 89(53.6%) and female was 77(46.4%). Distribution of duration of disease among patients 12-24 hours 80(48.2%) and more than 24 hours 86(51.8%) was 100(52.4%). Family History of coronary artery disease (CAD) 84(50.6%), diabetes mellitus 93(56.0%), hypertension 110(66.3%) and smoking status was 118(71.1%). Distribution of ventricular tachycardia was present among 103(62.0%) patients and was absent in 63(38.0%) patients. Conclusions: Ventricular tachycardia is the most common tachycardia occurring in patients in the first 48 hours who sustained myocardial infarction. It was shown that bradyarrhythmia was more common in patients with inferior wall myocardial infarction while ventricular tachycardia was found to be more in patients with anterior wall myocardial infarction.